Features of the clinical course of generalized periodontitis in patients with primary hypothyroidism - Kolenko Ю. Г.; Kolesova Н. В.; Revych В. О. (Actual Dentistry, 2024)
Actuality. Various pathogenetic relationships of general somatic pathology and diseases of the mucous membrane of the oral cavity, periodontium, and teeth dictate the need for a differentiated, personalized approach to their diagnosis and the choice of prevention and treatment tactics. The aim of the study. To study the peculiarities of periodontal status against the background of primary hypothyroidism. Materials and methods. The object of the study was 82 peopl eaged 28–47 years who applied to the Dental Medical Center of NMU. O. O. Bogomolets for the purpose of examination and remediation and had periodontal complaints. Of them, 51 had a confirmed diagnosis of primary hypothyroidism (manifest). The examination was carried out by standard clinical methods. Research results. It was established that the patients of the main group had a more severe degree of periodontal tissue damage and more often required a comprehensive periodontal examination and treatment. The fact of the rapid progression of the inflammatory process in the gums with the destruction of the clinical attachment and its rapid transformation into the inflammatory-destructive one has been established. Also characteristic are clearly pronounced signs of dystrophic processes, which are expressed in the generalized recession of the gums and their thinning. Conclusions. It has been established that the course of periodontitis against the background of primary hypothyroidism has a number of features caused both by the direct effect of insufficient thyroid hormones and by the specific effect of replacement therapy on the condition of periodontal tissues.